2014
DOI: 10.1017/s2040174414000531
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine during pregnancy: changes induced in neurotransmission, which could heighten proclivity to addict and induce maladaptive control of attention

Abstract: Prenatal exposure to nicotine, occurring either via maternal smoking or via use of transdermal nicotine patches to facilitate cigarette abstinence by pregnant women, is associated with ∼ 13% of pregnancies worldwide. Nicotine exposure during gestation has been correlated with several negative physiological and psychosocial outcomes, including heightened risk for aberrant behaviors involving alterations in processing of attention as well as an enhanced liability for development of drug dependency. Nicotine is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 113 publications
(210 reference statements)
0
11
0
3
Order By: Relevance
“…In recent years, a growing body of clinical, epidemiological and experimental studies testify to a crucial role of gestational factors in brain development and functioning in postnatal life, which increases its vulnerability to later development of neurodegenerative disorders including Parkinson's and Alzheimer's diseases (Faa et al, 2014 ). It has clearly been demonstrated that factors such as diet, infectious disease, drug administration, smoking and alcohol consumption, as well as persisting maternal stress, significantly affect fetal brain development and its function after birth (for review see Charil et al, 2010 ; Li et al, 2012 ; Monk et al, 2013 ; Donald et al, 2015 ; Gawałek and Sliwowska, 2015 ; Kohlmeier, 2015 ; Labouesse et al, 2015 ). The periods of prenatal development and early postnatal life are extremely important for formation of brain structures which will be involved in cognitive functions, including learning and memory, and shape life experience and character of individuals (Babenko et al, 2015 ; Desplats, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a growing body of clinical, epidemiological and experimental studies testify to a crucial role of gestational factors in brain development and functioning in postnatal life, which increases its vulnerability to later development of neurodegenerative disorders including Parkinson's and Alzheimer's diseases (Faa et al, 2014 ). It has clearly been demonstrated that factors such as diet, infectious disease, drug administration, smoking and alcohol consumption, as well as persisting maternal stress, significantly affect fetal brain development and its function after birth (for review see Charil et al, 2010 ; Li et al, 2012 ; Monk et al, 2013 ; Donald et al, 2015 ; Gawałek and Sliwowska, 2015 ; Kohlmeier, 2015 ; Labouesse et al, 2015 ). The periods of prenatal development and early postnatal life are extremely important for formation of brain structures which will be involved in cognitive functions, including learning and memory, and shape life experience and character of individuals (Babenko et al, 2015 ; Desplats, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…GABARmediated alterations in activity likely play a role in LDT functioning within local circuits, and/or could significantly influence output from the LDT projection neurons, including to targets in the mesoaccumbal, mesocortical and corticothalamic pathways. Therefore, alterations in GABAergic neurotransmission within the LDT could contribute to aversive effects on behavioral and cognitive outcomes associated with PNE that are suspected to involve alterations in mesocorticolimbic and thalamocortical processing (Cornelius & Day, 2009;Dwyer et al, 2009;Kohlmeier, 2015;Lacy et al, 2014;Paz et al, 2007;Smith et al, 2010). Although alterations in GABAergic-mediated transmission from the LDT have not been shown to play a crucial role in PNE-associated negative behavioral outcomes, GABARs within the mesopontine tegmentum have been suggested to play a role in the mediation of behaviors and emotion via their presence on mesoaccumbal, mesocortical and thalamic LDT projection neurons (Arnaud, Gauthier, & Gottesmann, 2001;Braun et al, 1997;Kantrowitz, Citrome, & Javitt, 2009;Kohlmeier et al, 2013;Maquet et al, 1996).…”
Section: Functional Significancementioning
confidence: 99%
“…Основной причиной активного исследования влияния никотина на организм человека являет-ся тот факт, что он входит в состав табачного дыма и считается опасным нейротоксином [96,110]. Никотин -конкурентный селективный агонист Н-холинорецепторов, легко проникает через гема-тоэнцефалический барьер [113] и абсорбируется в грудном молоке [41,61].…”
Section: пренатальные эффекты никотина на эмбриональное развитие и отunclassified
“…Любые нарушения в этой систе-ме, возникающие во время беременности, могут вызывать ту или иную патологию либо формировать у потомков новые функциональные системы с из-менением адаптивного поведения и социальных взаимо отношений [11,65,96,155].…”
unclassified
See 1 more Smart Citation